2017
DOI: 10.1038/srep45291
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis indicates that mitochondrial energy metabolism in skeletal muscle tissue is negatively correlated with feed efficiency in pigs

Abstract: Feed efficiency (FE) is a highly important economic trait in pig production. Investigating the molecular mechanisms of FE is essential for trait improvement. In this study, the skeletal muscle proteome of high-FE and low-FE pigs were investigated by the iTRAQ approach. A total of 1780 proteins were identified, among which 124 proteins were differentially expressed between the high- and low-FE pigs, with 74 up-regulated and 50 down-regulated in the high-FE pigs. Ten randomly selected differentially expressed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 28 publications
4
34
0
1
Order By: Relevance
“…However, RES lambs showed more accumulation of fat in several depots including the liver (Table 2) and intramuscular fat (Santos et al, 2018), which might be related to inhibition of β-oxidation (e.g., down accumulation of enoyl-CoA hydratase, mitochondrial isoform X2, in RES lambs), accumulation of upstream metabolites, and hence impaired fatty acid catabolism for energy production (Alexandre et al, 2015;Fu et al, 2017;Santos et al, 2017). In agreement with this hypothesis, liver fat accretion (as occurred in the RES lambs) has also been related to severe impairment of mitochondrial lipid metabolism mainly promoted by a deficiency in adenosine kinase (Boison et al, 2002), an enzyme which was also reduced in the liver of the RES lambs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, RES lambs showed more accumulation of fat in several depots including the liver (Table 2) and intramuscular fat (Santos et al, 2018), which might be related to inhibition of β-oxidation (e.g., down accumulation of enoyl-CoA hydratase, mitochondrial isoform X2, in RES lambs), accumulation of upstream metabolites, and hence impaired fatty acid catabolism for energy production (Alexandre et al, 2015;Fu et al, 2017;Santos et al, 2017). In agreement with this hypothesis, liver fat accretion (as occurred in the RES lambs) has also been related to severe impairment of mitochondrial lipid metabolism mainly promoted by a deficiency in adenosine kinase (Boison et al, 2002), an enzyme which was also reduced in the liver of the RES lambs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thiamin supplementation in dairy cattle has been reported to increase rumen pH and balance the population of lactic acidproducing and -consuming bacteria (Wang et al, 2015). Thiamine is critical for cellular function, as its phosphorylated and active form, thiamine diphosphate (TDP), acts as a coenzyme for three key enzymes in glucose metabolism (Liu et al, 2017) which differs to a great extent in high and low feed efficient groups (Fu et al, 2017). From DHFE, the genes CRB1 (chr 10), DLG2 (chr 9), PARD6G (chr 6), and PPP1CB (chr 3) pointed towards the hippo signaling pathway.…”
Section: Mtor and Mapk: Key Signaling Pathways In Durocmentioning
confidence: 99%
“…An earlier duodenal transcriptomic analysis in chickens showed that the difference in RFI may be related to digestibility, metabolism and biosynthesis processes as well as energy homeostasis [8]. Moreover, A previous high throughput sequencing analysis indicates that mitochondrial energy metabolism in skeletal muscle plays a key role in the regulation of feed efficiency [9,10]. Skeletal muscle plays a particularly important role in the utilization and storage of carbohydrates and lipids from feed [11].…”
Section: Introductionmentioning
confidence: 99%